2019
DOI: 10.1002/srin.201900194
|View full text |Cite
|
Sign up to set email alerts
|

Characterization Transformation of Inclusions Using Rare Earth Ce Treatment on Al‐Killed Titanium Alloyed Interstitial Free Steel

Abstract: By using the thermodynamic calculation of evolution of inclusions that contain rare earths, industrial‐scale modification experiments are conducted. Energy spectroscopy analysis, field emission scanning electron microscopy, energy dispersive spectrometry, original morphology analysis, and Factsage 7.2 software are used to analyze the evolution mechanisms of inclusions in Al‐killed titanium‐alloyed interstitial free steel. The results reveal that different substances are formed in the following order: Ce2O3(s) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…4. 17) It can be seen from the figure that when the content of the rare earth Ce is less than 0.01%, only CeAlO 3 , Ce 2 O 3 , Ce 2 O 2 S, and CeO 2 are formed. When Table 3.…”
Section: Thermodynamic Calculation Of the Formation Ofmentioning
confidence: 93%
See 1 more Smart Citation
“…4. 17) It can be seen from the figure that when the content of the rare earth Ce is less than 0.01%, only CeAlO 3 , Ce 2 O 3 , Ce 2 O 2 S, and CeO 2 are formed. When Table 3.…”
Section: Thermodynamic Calculation Of the Formation Ofmentioning
confidence: 93%
“…After adding rare earth Ce in the later stage of refining, due to the fact that the Gibbs free energy of activity O and S in Ce and steel is much lower than that of Al and O (Table 3), it is easy to form rare earth oxysulfide. 17,24,25) Al 2 O 3 particles are transformed into rare earth oxides by oxygen extraction and combined with other composite inclusions. Some rare earths even combine with oxygen in Al 2 O 3 directly to form Al-O-Ce and other compounds.…”
Section: Effect Of Ce On Transformation Mechanism and Distribution Ofmentioning
confidence: 99%
“…5(e)) is enriched on the reaction interface with a good coupling correspondence, which proves that the Ce 2 O 3 is formed through the reaction between Ce and O on the interface. The Ce-Fe binary phase diagram calculated by FactSage 7.2 using the thermodynamic database of RE-X binary alloy [24][25][26][27][28][29][30] is employed to reveal the evolution process of phases during the melting process, as shown in Fig. 6.…”
Section: Melting Process Of Cerium Ferroalloy In the Molten Steelmentioning
confidence: 99%
“…In order to study the application of rare earth elements in a more comprehensive and systematical way, some researchers [24][25][26][27][28][29] have developed the thermodynamic database for the binary alloy system RE-X (RE: Ce, La, Gd, Nd, Sm, Lu, Ho, Er; X: Ag, Cr, Mn, V, Zn, Bi). However, few detailed results were reported on an actual melting process and the reaction behavior between cerium ferroalloy and molten steel.…”
Section: Introductionmentioning
confidence: 99%
“…Cai and Li [ 20 ] studied the effect of Ce addition on inclusions in AISI 202 stainless steel, and found that when the content of Ce is among 0.011 and 0.016 wt%, the spherical multiphase inclusions containing CeAlO 3 and Ce 2 O 2 S form. Wang et al [ 21,22 ] experimentally investigated the effect of Ce addition on the nonmetallic inclusions in Al‐killed spring steel and pointed out with the addition of Ce, Al 2 O 3 inclusion is modified via the route of Al 2 O 3 → Ce 2 O 3 Al 2 O 3 → Ce 2 O 2 S, but the Al 2 O 3 ·MgO spinel inclusion is modified via the route of Al 2 O 3 ·MgO →Ce 2 O 3 Al 2 O 3 ·MgO or Ce 2 O 2 SAl 2 O 3 ·MgO → Ce 2 O 3 or Ce 2 O 2 S. Gao et al [ 23 ] investigated the inclusion modification mechanism in Al‐killed IF steel with the addition of Ce with thermodynamic calculation and industrial experiment and concluded that after Ce treatment, the irregular Al 2 O 3 inclusions were first surrounded with rare‐earth Ce and then gradually modified into spheroidal CeAlO 3 , Ce 2 O 3 , and Ce 2 O 2 S inclusions. Huang et al [ 24 ] carried out plant trials and thermodynamic calculation to investigate the effect of Ce on the inclusions in H13 steel and concluded that the Al 2 O 3 ·MgO spinel inclusion is effectively modified into cerium oxide (CeO) and cerium oxy‐sulfide (CeOS).…”
Section: Introductionmentioning
confidence: 99%